Selection of excipients for the purpose of creating an intranasal gel of interleukin-1 receptor antagonist β (IL-1ra) - B. S. Burlaka; I. F. Bielenichev; V. V. Hladyshev; E. V. Suprun; H. P. Lysianska (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
There is a negative dynamic of the spread of cerebrovascular diseases, which often lead to disability or death in patients in the world, today. Such diseases are characterized by acute disorders of cerebral metabolism and blood circulation, against the background of other chronic pathologies. More than one hundred thousand cases of stroke are registered in Ukraine every year, with more than thirty percent of patients dying within the first month of the disease according to the Center for Medical Statistics of the Ministry of Health of Ukraine.